Characterization of mango (Mangifera indica)-growing soils and soil-related constraints for production in south Karnataka - NAIDU, L G K; REDDY, R S; RAJA, EDWARD; PRASAD, C R SHIVA; KRISHNAN, P (The Indian Journal of Agricultural Sciences, 2013)
A field survey Was earned out in February 1992 to characterize and diagnose the soil-related constraints of mango (Mangifera indica L) growing in red and lateritic soils of south Karnataka. Eleven soils studied varied widely in their morphology and physico-chemical characteristics. The soils were categorized low, medium and high for N, P and K fertility status. Soil depth, coarse fragments, erosion and surface ron-off were the major soil-related constraints. Most of the orchards were found suffering from K deficiency. Leaf-tip and marginal chlorosis and scorching on older leaves were some of the typical symptoms of K deficiency, ’Bangalora’ and ’Neelum’ cultivars were found most susceptible to it.